1998
DOI: 10.1212/wnl.51.3.734
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the prion protein is associated with cognitive impairment in the elderly

Abstract: This observation suggests that variability of the PRNP locus may be associated with cognitive performance in the elderly. This result, if confirmed, offers potential clues for the role of PRNP in the human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 13 publications
2
42
1
4
Order By: Relevance
“…Codon 129 homozygosity is a well-known risk factor for CJD [23] and was demonstrated recently to be a risk factor in other dementia as well. Codon 129 homozygosity for methionine is associated with AD [24] and for valine with a risk of cognitive decline [25,26]. A study has demonstrated that AD brains are characterized by an increase of intraneuronal PrP c immunoreactivity compared to controls [27].…”
Section: Discussionmentioning
confidence: 99%
“…Codon 129 homozygosity is a well-known risk factor for CJD [23] and was demonstrated recently to be a risk factor in other dementia as well. Codon 129 homozygosity for methionine is associated with AD [24] and for valine with a risk of cognitive decline [25,26]. A study has demonstrated that AD brains are characterized by an increase of intraneuronal PrP c immunoreactivity compared to controls [27].…”
Section: Discussionmentioning
confidence: 99%
“…In case of polymorphism at codon 219 of the PRNP gene in which lysine is substituted for glutamic acid (E219K), the K allele was found to be protective against sporadic CJD in Asia and Pacific (Soldevila et al, 2003). Berr et al (1998) observed the correlation bet-ween the codon 129 polymorphisms and cognitive performance. Risk of cognitive impairment was increased significantly in VV individuals compared with either MV or MM subjects.…”
Section: Introductionmentioning
confidence: 98%
“…Although reports show contradictory results, this polymorphism has been associated with different phenotypes in prion diseases and other neurodegenerative diseases [3][4][5][6][7][8] . The homozygosity for V was associated with higher risk of cognitive impairment in two large populational studies 28,29 . On the other hand, the homozygosity for M was also associated with lower scores on cognitive tests in cognitive normal population 30 .…”
Section: Discussionmentioning
confidence: 94%
“…The codon 129 polymorphism of PRNP has been associated with AD and cognitive performance in the elderly population 19,28 . Although reports show contradictory results, this polymorphism has been associated with different phenotypes in prion diseases and other neurodegenerative diseases [3][4][5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%